La Costituzione siciliana del 1812 - Angelo Grimaldi (Revista de Derecho)
The Sicilian Constitution of 1812 was included in a Political System which can be defined as “monarchy restrict” because the political power was mainly in the hands of the Sovereign and the parliament only intervened to put some limits on the “potere regio”. The sicilian constitutional experience of 1812 wasn’t a breaking off from the constitution, it remained a dualistic system in which the King had legitimate dynasty and most of the members of the Parliament belonged to the Sicilian Nobility. The Par - liament didn’t represent the nation because the two main governing bodies were the Sovereign and the aristocrats: the “nation”, being an abstract juridical bodies couldn’t govern directly but only through delegation; consequently the Parliament could repre - sent only a part of the Sicilian Society, that is to say only that fraction that was repre - sented in the Parliament. The Sicilian Parliament of 1812 it cannot be considered as constituent assembly due to the way meetings were called, election and social make up of its members. And therefore canot be considered as expression of constituent power. The Constitution provider for separation of powers but the English Constitutionl mo - del couldn’t be put into practice because it was based on royal assent, (the King can do no wrong) and this interna corporis whic would be led to the impeachment as being a political responsibility not a juridical responsibility. There was the addiction of feudalism but all feudal possession were transformed in Habeas corpus. The Constitution transformed the juridical regime of large landed estates from feudal Homage to freeholder homage.